Diagnosis and management of hypovolemic shock in children - Rybojad, Beata; Aftyka, Anna; Rudnicka-Drożak, Ewa (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2012)
Hypovolemic shock is characterized by insufficient tissue perfusion due to a decreased intravascular volume, resulting from the loss or inadequate fluid intake. Diagnosis becomes even more difficult for many reasons if a child is the patient. It is important to take action early, before the hypotension occurs, which is a late symptom of shock in a pediatric patient. This article aims to explain specifics of the hypovolemic shock in children and provide practical guidance taking into consideration the Guidelines of the 2010 European Resuscitation Council and a European guideline for management of bleeding following major trauma.